1983
DOI: 10.1051/rnd:19830511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amylomaize starch on cholesterol and bile acid metabolisms in germfree (axenic) and conventional (holoxenic) rats

Abstract: Summary. Germfree and conventional rats were given a semi-synthetic diet containing either normal cornstarch or an amylomaize starch. The experimental groups thus formed were compared to assess the effects of these two types of starch and to determine if digestive tract microflora was involved in these effects.The presence of amylomaize starch decreased body growth in germfree and conventional rats, increasing food intake in the former and decreasing it in the latter. In conventionals, amylomaize starch decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 4 publications
3
19
0
1
Order By: Relevance
“…In addition, liver cholesteryl ester concentrations were also decreased (Table 1). These effects of amylomaize diet in Zucker rats were similar to those previously reported in conventional or germ-free rats of the Fisher strain [6].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition, liver cholesteryl ester concentrations were also decreased (Table 1). These effects of amylomaize diet in Zucker rats were similar to those previously reported in conventional or germ-free rats of the Fisher strain [6].…”
Section: Discussionsupporting
confidence: 78%
“…Hypocholesterolemic effects of starch feeding have been previously observed in rats and rabbits fed potato starch [5] . Recently it was reported that a diet containing an amylomaize starch decreased plasma cholesterol levels by about 40% in conventional or in germ-free rats [6]. However, this study did not examine the precise effects of this starch on the different plasma lipoproteins.…”
mentioning
confidence: 41%
See 1 more Smart Citation
“…Similar observations have also been reported for various other poorly digestible carbohydrates and have been related to the decrease in caecal pH in CV rats fed these carbohydrates and to a modification of the bacterial population in the large intestine (Andrieux et al, 1989). It was also noted that, with amylomaize starch compared with normal starch, caecal size increased 4-fold in CV rats (Sacquet et al, 1983).…”
Section: Discussionsupporting
confidence: 70%
“…As reported in a previous experiment with lactose (Meslin et al, 1981 there was no relation between bile acid pool and epithelial renewal because a similar increase in bile acid pool was observed in CV and GF rats fed amylomaize starch (Sacquet et al, 1983;Andrieux et al, 1989) whereas epithelium renewal was modified only in CV rats.…”
Section: Discussionmentioning
confidence: 53%